PENGARUH FAKTOR SOSIAL DAN ETIKA DALAM PERILAKU PENGAMBILAN KEPUTUSAN INVESTASI: STUDI KASUS PADA INVESTASI KEUANGAN SYARIAH - Hamizar, Arizal (IAIN Ambon, 2023)
AbstractThis study examines how ethical and social responsibility factors influence investment decision-making among Islamic finance investors. Utilizing a qualitative approach, an analysis of investors' perceptions and preferences regarding investment is conducted, connecting them with the principles of Islamic finance. The results of in-depth interviews with a diverse group of investors reveal that the principles of Islamic finance serve as a strong ethical guide in investment decision-making. Moreover, it is found that ethical and social responsibility values are increasingly playing a significant role in guiding the selection of investment instruments. The importance of ethics in Islamic finance investment is reflected in investors' emphasis on the principles of Islamic finance that prohibit usury, ambiguity, and gambling. However, the findings also uncover that investors are increasingly considering the social impact of their investments. Social responsibility is deemed a determinant factor in decision-making, with preferences tending to shift towards investment instruments that provide positive benefits to society and the environment.Keywords: Financial Investment, Islamic Finance, Consumer Behavior, Social, Ethics. AbstrakPenelitian ini mengkaji bagaimana faktor etika dan tanggung jawab sosial mempengaruhi pengambilan keputusan investasi di kalangan investor keuangan syariah. Dengan menggunakan pendekatan kualitatif, analisis mengenai persepsi dan preferensi investasi para investor dilakukan, serta menghubungkannya dengan prinsip-prinsip keuangan syariah. Hasil wawancara mendalam dengan beragam investor mengungkapkan bahwa prinsip-prinsip keuangan syariah menjadi panduan etika yang kuat dalam pengambilan keputusan investasi. Selain itu, ditemukan nilai-nilai etika dan tanggung jawab sosial semakin memainkan peran yang signifikan dalam memandu pemilihan instrumen investasi. Pentingnya etika dalam investasi keuangan syariah tercermin dalam penekanan investor terhadap prinsip-prinsip keuangan syariah yang melarang riba, gharar, dan maisir. Namun, temuan juga mengungkapkan bahwa investor semakin mempertimbangkan dampak sosial dari investasi mereka. Tanggung jawab sosial dianggap sebagai faktor penentu dalam pengambilan keputusan, dengan preferensi yang cenderung beralih ke instrumen investasi yang memberikan manfaat positif bagi masyarakat dan lingkungan.Kata Kunci: Investasi Keuangan, keuangan Syariah, Perilaku Konsumen, Sosial, Etika.